Experimental Analysis and Failure Criterion of Plain Concrete Subjected to Biaxial Loading under Fixed Lateral Loading - Zhenpeng Yu; Xue Sun; Furong Li (Advances in Civil Engineering)
By using a rock true triaxial apparatus hydraulic servo machine, biaxial loading experiments including biaxial compression-compression and biaxial compression-tension with fixed lateral loading on plain concretes were conducted and the stress-strain curves of plain concrete under various stress ratios were obtained. After determining the peak principal stress, the damage modes of plain concrete under various stress ratios were analyzed and the law of strength in the principal stress direction was studied as well. The experimental findings show that, under the fixed lateral loading, the failure modes of plain concrete under biaxial compression-compression and biaxial compression-tension are very similar to those under the equal proportional loading, but with higher amplitude of variation. In this paper, Kupfer’s classical failure criterion was applied to verify the experimental data and the predicted biaxial loading on plain concrete under fixed lateral loading and was regarded as relatively conservative. Meantime, based on Kupfer’s failure criterion and octahedral stress space, two different failure criteria had been proposed and verified. The results show that the proposed failure criteria have good applicability. The failure mechanism under fixed lateral loading was discussed and compared with that under the equal proportional loading method. This research is meaningful to plain concrete engineering application and calculation.